Studies on Some Physico-Chemical Characteristics of Ground Water Used in Some Rural Areas of Hardwar - Goel, Anjali (Asian Journal of Chemistry, 2010)
The physico-chemical studies of ground water of some villages of Hardwar, Uttaranchal, India has been made for parameters as pH, conductivity, turbidity, total hardness, ammonia, nitrate, chloride, sulphate and some metal ions. It was found that these water samples are not suitable for drinking purpose as they have high dissolved ions concentration, alkalinity, total hardness etc.